2011
DOI: 10.1002/apj.570
|View full text |Cite
|
Sign up to set email alerts
|

The surface structure and chemical characters of activated carbon fibers modified by plasma

Abstract: Viscose-based activated carbon fibers (VACFs) were treated by a direct-current (DC) discharge plasma at different conditions. The surface functional groups of VACFs were modified to improve the adsorption and catalysis capacity for SO 2 and NO x . The surface properties of the untreated and treated VACFs which were modified in different feed gases (air, O 2 , N 2 and NH 3 ) were performed by scanning electron microscopy, BET, X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared attenuated tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…These active species can modify the carbon surface by introducing oxygen‐containing groups, especially through the creation of carboxyl groups (COOH). [ 22 ] The mechanisms of functional group generation on the surface of CBMs have been elucidated by previous studies (Figure 1b). [ 13,23 ] A plausible mechanism can be summarized as follows.…”
Section: Effect Of Discharge Gas On Cbmsmentioning
confidence: 99%
“…These active species can modify the carbon surface by introducing oxygen‐containing groups, especially through the creation of carboxyl groups (COOH). [ 22 ] The mechanisms of functional group generation on the surface of CBMs have been elucidated by previous studies (Figure 1b). [ 13,23 ] A plausible mechanism can be summarized as follows.…”
Section: Effect Of Discharge Gas On Cbmsmentioning
confidence: 99%
“…However, the poor dispersion of CF in pulp, interfacial properties between CF and pulp, and the mechanical properties of the resulting paper have been major issues with the use of carbon fiber-based paper, such that it is necessary to modify the CF. The previous studies have shown that acid oxidation, coupling agents, polymer resin coating, -ray irradiation, and plasma treatment can improve the CF surface (Zhou et al 2012;Encinas et al 2014). Acid oxidation (HNO3, H2SO4, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…This special theme can be divided into four research groups, which are described as follows: The first group of papers covers a wide spectrum of coal science and technology, including the gasification reactivity of coal‐char, characterization of coal surface functional group, NOx emission control from coal‐fired power stations by methane reburn, ignition characteristics of coal during oxy‐fuel combustion, and techno‐economic analysis of coal‐fired power plant with post‐combustion CO 2 capture equipments. The second group provides insights into key issues associated with biomass utilization, such as combustion mechanisms of biomass, development of biosorbents for waste water treatment, biodiesel production and the emission of heavy metals during waste incineration. The third group focuses on the solid mixing mechanisms in a bubbling fluidized bed reactor. The fourth group investigates the characterization of activated carbon fiber modified by plasma.…”
Section: An Overview Of Papers In This Special Themementioning
confidence: 99%